Celjenje kostnine čeljustnic po puljenju zob - Gluvič, Maja (Medicinski razgledi, 2003)
The healing process after tooth extraction ends approximately 60 days after extraction. The stability of the alveolar-bone height and the density of the reformed bone show the success of the process. In research, bone healing is evaluated clinically and radiologically two months following tooth extraction.In analyzing alveolar bone height, geometric analysis via comparison of two roentgenograms was used. The roentgenogram before extractionwas used for measurement and calculation of the two-dimensional bonedefect following tooth extraction. On the second roentgenogram, which shows the alveolar ridge two months after tooth ex traction, the actual heightof the reformed bone was measured and compared with the height of bone failure immediately after extraction. The rate of the healing process was expressed as a percentage. The roentgenogram obtained after tooth extraction was scanned; the density of reformed bone was measured with the aid of a computer program and compared to that of the surrounding bone. The average height of bone healing was found to be 87.1%. The best healing process (97.5%)is seen in patients between 10 and 20 years; it decreases with age. Alveolar sockets with the lowest ability to heal (81.3%) were found in patients aged 61 to 70 years. The results of bone healing regarding the presence (or absence) of the surrounding teeth show the highest alveolar socket healing tendency in the presence of both surrounding teeth (97.4%), andthe lowest healing tendency in cases where the alveolar socket did not haveany surrounding teeth (82.2%). It was established that anterior maxillary teeth have the lowest bone healing tendency. The measurement of reformed bone density in healed alveolar sockets showed an average value of 82% and decreased with age with a high rate of statistical significance, the regression coefficient being 3.6 x 10-7. (Abstract truncated at 2000 characters).
Keywords: Rana, celjenje; Tooth Extraction; Wound Healing; Zobna ekstrakcija; Čeljust; Jaw; Kost, gostota; Bone Regeneration; Kost, regeneracija; Dental Arch; Starostni faktorji; Radiography; Zobni lok; Bone Density; Time Factors; Časovni faktorji; Age Factors; zobozdravstvo; zobje; puljenje; rane; celjenje; kostnina